The consequences of the Russian-Ukrainian War on the Ukrainian Education System - Lika Lagvilava (International Society of Philosophy and Cosmology, 2023)
The Russia-Ukraine war that started in 2022 has affected the education system of Ukraine. It was preceded by a period of pandemic. The impact of war on education goes beyond a humanitarian crisis; It also threatens the future of the entire generation of Ukrainians in terms of education, because education is a priority direction that has no alternative. An educated generation creates a strong future for the country. In this sense, war has no winners. The hostilities disrupt the normal rhythm of life, which affects all spheres. The emotional state of war children is very significant and attention-grabbing. It is a pity when in the 21st century war is no stranger to children. Children have to overcome difficulties in front of this harsh reality.